Programming Languages and Systems 19th European Symposium on Programming, ESOP 2010, Held as Part of the Joint European Conferences on Theory and Practice of Software, ETAPS 2010, Paphos, Cyprus, March 20-28, 2010. Proceedings - Gordon, Andrew D.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 19th European Symposium on Programming, ESOP 2010, held in Paphos, Cyprus, in March 2010, as part of ETAPS 2010, the European Joint Conferences on Theory and Practice of Software. The 30 revised full papers, presented together with two invited talks (one abstract and one full), were carefully reviewed and selected from 121 full paper submissions. The topics addressed include programming paradigms and styles, methods and tools to write and specify programs and languages, methods and tools for reasoning about programs, methods and tools for implementation, and concurrency and distribution.
The Audacity of Hope: Thoughts on Reclaiming the Database Dream -- Dynamic Boundaries: Information Hiding by Second Order Framing with First Order Assertions -- Coupling Policy Iteration with Semi-definite Relaxation to Compute Accurate Numerical Invariants in Static Analysis -- Precise and Automated Contract-Based Reasoning for Verification and Certification of Information Flow Properties of Programs with Arrays -- A Semantic Framework for Declassification and Endorsement -- Amortised Resource Analysis with Separation Logic -- A PolyTime Functional Language from Light Linear Logic -- Testing Polymorphic Properties -- Formal Verification of Coalescing Graph-Coloring Register Allocation -- A Theory of Speculative Computation -- Propositional Interpolation and Abstract Interpretation -- Functional Programming in Sublinear Space -- Logical Concurrency Control from Sequential Proofs -- Fluid Updates: Beyond Strong vs. Weak Updates -- Parameterized Memory Models and Concurrent Separation Logic -- Amortized Resource Analysis with Polynomial Potential -- Generative Operational Semantics for Relaxed Memory Models -- Automating Security Mediation Placement -- TRX: A Formally Verified Parser Interpreter -- On the Expressive Power of Primitives for Compensation Handling -- Separating Shape Graphs -- Deadlock-Free Channels and Locks -- Verifying a Compiler for Java Threads -- A Grammar-Based Approach to Invertible Programs -- Faulty Logic: Reasoning about Fault Tolerant Programs -- A Hoare Logic for the Coinductive Trace-Based Big-Step Semantics of While -- A Universal Calculus for Stream Processing Languages -- Enforcing Stateful Authorization and Information Flow Policies in Fine -- Stateful Contracts for Affine Types -- CFA2: A Context-Free Approach to Control-Flow Analysis -- Weighted Dynamic Pushdown Networks -- Explicit Stabilisation for Modular Rely-Guarantee Reasoning.
Keywords: Computer science; Computer Communication Networks; Software engineering; Logic design; Artificial intelligence; Computer Science; Software Engineering; Computer Communication Networks; Logics and Meanings of Programs; Programming Techniques; Programming Languages, Compilers, Interpreters; Artificial Intelligence (incl. Robotics).